Cloud Computing in The World and Türkiye: Challenges, Opportunities and A Path Forward - Dinçer, Gönül; Toro, Havva Serim; Söylemez, Seniha Alev; Atan, Murat; Emirmahmutoğlu, Furkan; Sercan, Mustafa Remzi (Holistence Academy Ar-Ge Yazılım Yayıncılık Eğitim Danışmanlık ve Organizasyon Ticaret Limited Şirketi, 2026)
Cloud Computing in the World and Türkiye: Challenges, Opportunities and a Path Forward presents a comprehensive analysis of the transformative power of cloud technology, both globally and in Türkiye. The report delves into essential cloud concepts, service models (SaaS, PaaS, IaaS), and deployment strategies while addressing critical global challenges such as data security and standardisation. With a focused lens on Türkiye, it evaluates the nation's current digital landscape by examining government policies, legal frameworks such as data localisation, and sectoral adoption rates across the public and private spheres. Concluding with a strategic SWOT analysis and actionable recommendations, this work serves as a vital roadmap for policymakers, business leaders, and researchers aiming to navigate Türkiye's digital future.